Human Resource Management Strategy in Supporting Madrasah Digitalization at MAN 2 Bireuen - Putri Marda Sari; Susi Yusrianti; Khairiani Khairiani (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
The digital transformation of madrasah education requires strategic management of human resources (HR) to ensure the success of digital-based learning and administration. However, limitations in digital competence, resistance to change, and lack of structured development programs remain challenges. This study aims to analyze HR management strategies in supporting madrasah digitalization at MAN 2 Bireuen. A qualitative-descriptive approach was employed, involving interviews, observation, and documentation with school principals, teachers, and educational staff as participants. The findings reveal that HR planning is conducted strategically through digital competence-based recruitment, indicating the institution’s commitment to adaptive and evidence-based staffing. HR organizing is implemented through a non-formal, competence-oriented team structure, though it poses risks of role ambiguity without clear accountability mechanisms. HR development is carried out comprehensively through formal training (RTM, Kemenag Pintar), self-directed learning, and in-class technical assistance. Finally, supervision is conducted through participatory evaluations in regular meetings, serving not only as performance assessment but also as a medium for collective reflection and continuous improvement. This study concludes that integrated and adaptive HR management is crucial for successful digital transformation in madrasahs, especially in regions with limited resources.